IMPLEMENTASI METODE ANFIS DATA MINING DALAM MENYELEKSI BEASISWA DI SMPN 7 SOROLANGUN - Raja Ayu Mahessya; Sulvia Indrawati (LPPM Universitas Dinamika Bangsa, 2017)
The author discusses the use of Adaptive Neuro Fuzzy Interference System (ANFIS) in implementing the Scholarship Selection Acquisition using ANFIS (Adaptive Neuro Fuzzy Interface System) or Adaptive Network-based Fuzzy Interface System for the withdrawal of its conclusions. ANFIS is an architecture that is functionally similar to the fuzzy rule base Sugeno models. It could be said that ANFIS is a method by which in adjusting the rules used learning algorithms on a set of data. The hope is to get knowledge of such data, obtained from the knowlage ANFIS method is the rule on Fuzzy Interface System (FIS). This study aims to predict students who received scholarships, so the school did not have to bother anymore to manually select students. Data for the training system focuses on three pieces of input value, Number of Dependents Parents and Parents Income; and 1 pc output is Earned Scholarship. From the results obtained training, web-based application created to determine Acquisition Scholarship based on the available quota. Then students can register online for the scholarship application process so that students easily access the information about scholarships